2014
DOI: 10.1093/brain/awu331
|View full text |Cite
|
Sign up to set email alerts
|

Increased PK11195-PET binding in normal-appearing white matter in clinically isolated syndrome

Abstract: The most accurate predictor of the subsequent development of multiple sclerosis in clinically isolated syndrome is the presence of lesions at magnetic resonance imaging. We used in vivo positron emission tomography with (11)C-(R)-PK11195, a biomarker of activated microglia, to investigate the normal-appearing white matter and grey matter of subjects with clinically isolated syndrome to explore its role in the development of multiple sclerosis. Eighteen clinically isolated syndrome and eight healthy control sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
73
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 40 publications
10
73
0
2
Order By: Relevance
“…In line with previous observations, we found increased TSPO levels in WM lesions 43, 44 and NAWM 16, 43, 45 . We found that TPSO levels in WM lesions, measured with both SUVR and DVR, were generally lower than those in cortical lesions.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In line with previous observations, we found increased TSPO levels in WM lesions 43, 44 and NAWM 16, 43, 45 . We found that TPSO levels in WM lesions, measured with both SUVR and DVR, were generally lower than those in cortical lesions.…”
Section: Discussionsupporting
confidence: 93%
“…In our MS cohort, neurological disability correlated with microglial/macrophages activation in deep GM, in addition to neuroinflammation in the cortex and WM as previously reported 14, 16 . Here, we also demonstrated that microglia/macrophages activation correlated with reduced cognitive performance in MS.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…[ 11 C]PK11195 PET has showed increased microglial activation in the cortical grey matter (GM) of relapsingremitting (RR) and secondary progressive (SP) MS patients, which correlated with levels of neurological disability [139]. Patients with clinically isolated syndrome showed a global increase of [ 11 C]PK11195 binding in normal-appearing white matter (NAWM), and the binding was higher in subjects who developed lesions that were disseminated in space or MS at 2 years follow-up [140]. [ 11 C]PK11195 PET has been found to be increased in chronic hypointense T1-weighted MRI lesions (black holes) and this has been associated with worse prognosis at 2 years of follow-up in progressive MS [141].…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Studies using magnetization transfer imaging suggest loss of macromolecules such as myelin, while diffusion imaging measures correlate with injured structural components within the tissue, including axons, myelin, and the tissue matrix. A recent study using PET showed that microglia are globally activated in the normal-appearing white matter and deep grey matter of patients with CIS compared to control subjects (Giannetti et al, 2015), and that the global increase in microglial activation is predictive of earlier development of multiple sclerosis over the next 2 years. This PET study is in accord with studies of autopsied multiple sclerosis tissues that have revealed activated microglia throughout normal-appearing white matter.…”
mentioning
confidence: 99%